Implikatur Percakapan Dalam Serial Gadis Kretek Sebagai Strategi Komunikasi Kesetaraan Gender - Revalina Aulia Ramadhani; Asep Purwo Yudi Utomo (Fakultas Bahasa dan Sastra Indonesia Universitas Jenderal Soedirman, 2025)
Dominance in the use of speech in dialogues between characters is caused by violations of the cooperative principle, resulting in differences in meaning between participants because it tends not to be expressed explicitly, but rather through implicit meaning. This study uses a pragmatic and qualitative descriptive approach. The method used to collect data in this study is the observation method, with further techniques including free observation involving conversation (SBLC) and note-taking techniques. The pragmatic subtypes equivalence method examines the first and second research problems. The study results found that the most dominant maxim violations of relevance are the quantity maxim, quality maxim, and manner maxim. As for conversational implicatures, the resistive implicature occupies the most dominant position with 35 data points and is mainly used by female characters in speech activities. Findings show that the female characters in the series use resistant and social criticism types of conversational implicature to reject patriarchal domination by negotiating more communicative autonomy, while male characters tend to use control-type conversational implicature to maintain authority in speech activities. The defensive-type implicature used by both parties indicates a need to maintain harmony in conversation.